A Toolkit for Corporate Workouts - World Bank (World Bank, Washington, DC, 2022)
This Toolkit is aimed primarily at policy makers, financial institutions, and enterprises. It examines different types of corporate restructuring procedures on the basis that one size does not fit across all jurisdictions. Recent experience of the operation of corporate restructuring regimes around the world demonstrates that such regimes must appropriately account for domestic considerations, including a jurisdiction’s institutional and regulatory framework. This Toolkit, a revised and updated version of the 2016 publication, incorporates wide-ranging updates that reflects this experience. It describes matters relevant to the adoption of workout frameworks for a broad range of types of corporate restructuring procedures, some of which provide for a role for courts or regulatory authorities. This widened perspective highlights considerations of particular relevance in the context of the COVID-19 pandemic, a crisis that makes restructuring viable businesses especially important.